Tinjauan Yuridis Terhadap Upaya Hukum Penyelesaian Sengketa Pemilihan Kepala Desa Berdasarkan Undang-Undang No 6 Tahun 2014 Tentang Desa - Kalvin Hasiholan Gultom; Margo Hadi Pura; Muhammad Rifaldi (Peneliti.net, 2022)
The village is one form of embodiment of regional autonomy adopted by our legal system in Indonesia. The election of village heads as representatives of regional autonomy and democracy in Indonesia aims to elect leaders who have the capacity to regulate authority, policy, and management of villages and village communities. The village head election is based on Law Number 6 of 2014 concerning Villages that the village head election is held by the village consultative body and is directly elected by the village community. In the implementation of village head elections, it is possible that there will be dissatisfaction from the contesting parties, causing conflicts and disputes. So the purpose of this study is to find out what and how the legal remedies for resolving village head election disputes are based on Law Number 6 of 2014 concerning this Village. The results of the study will show how legal remedies are in resolving village head disputes and who has the authority to resolve this village head election dispute based on Law No. 6 of 2014 concerning this Village and also implementing regulations and local government regulations because this is the authority local government. So that local governments must make and facilitate rules regarding village head elections in a comprehensive and concrete manner so that there is legal certainty and it is also necessary to establish an ad hoc judicial body that is authorized to resolve village head election disputes.